1999
DOI: 10.1093/humrep/14.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic abnormalities and spermatogenic parameters in severe oligoasthenozoospermia

Abstract: The incidence of meiotic abnormalities and their relationship with different spermatogenic parameters was assessed in 103 male patients with presumably idiopathic severe oligoasthenozoospermia (motile sperm concentration < or = 1.5 x 10(6)/ml). Meiosis on testicular biopsies was independently evaluated by two observers. Meiotic patterns included normal meiosis and two meiotic abnormalities, i.e. severe arrest and synaptic anomalies. A normal pattern was found in 64 (62.1%), severe arrest in 21 (20.4%) and syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 16 publications
4
44
0
3
Order By: Relevance
“…Our study shows that an FSH concentration higher than 10 UI/ml was a predictive factor of meiotic abnormalities. Our data are in accordance with the data of Vendrell et al [27] and Faure et al [16] who showed that an elevated FSH level is significantly correlated with higher risk of high sperm disomy rates. In addition the total rate of sex chromosomes aneuploidy was found to be significantly increased in patients exposed to an elevated temperature.…”
Section: Discussionsupporting
confidence: 94%
“…Our study shows that an FSH concentration higher than 10 UI/ml was a predictive factor of meiotic abnormalities. Our data are in accordance with the data of Vendrell et al [27] and Faure et al [16] who showed that an elevated FSH level is significantly correlated with higher risk of high sperm disomy rates. In addition the total rate of sex chromosomes aneuploidy was found to be significantly increased in patients exposed to an elevated temperature.…”
Section: Discussionsupporting
confidence: 94%
“…They observed high sex chromosome aneuploidy rates (0.68%) in the sperm of Robertsonian translocation carriers compared to controls (0.37%) and insignificant rates for other chromosomes. Some investigations have shown an ICE [22,23], but 4 was not possible because of the extremely low sperm concentration (0.14 × 10 6 /μl) that could be related to aneuploidy and diploidy. Most carriers of Robertsonian translocations have oligozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Even among infertile men with a normal blood karyotype, the frequency of chromosomal abnormalities restricted to the germ line is considerable. 17,18 Furthermore, infertile men with impaired spermatogenesis may have an increased risk of producing aneuploid germ cells as a consequence of chromosomal pairing and/or disjunction errors during mitosis and/or meiosis 15,19 which may constitute the underlying pathogenetic cause of the increased sperm aneuploidy rate found in patients with abnormal semen parameters. So it seems likely that patients with a more severe spermatogenetic impairment, such as those with NOA, are more prone to mitotic and/or meiotic errors during cell division and proliferation.…”
Section: Discussionmentioning
confidence: 99%